Annual Plan 1994-95 Tripura State Part I - Planning Commission (Planning Commission, 1994)
The Demographic picture of the State presents the effects of uninterrupted influx from across the border. the decennial population increase in the State during the period 1981-9.1 (34.30%)has been more than that for the preceding decade, unlike that for the country. the population increased in Tripura during the decade 1981-91 has been more than that in the North Eastern States of Assam (24.24%), Manipur (29.29%) and Meghalaya (32.86%) but less than that in the States of Nagaland (56.08%), Mizoram (39.7%),and Arunachal Pradesh (36.83%). the growth of population is not entirely accounted for by natural growth.
Planning and Development Department, Government of Tripura